Calidad De La Tarea Escolar Y Rendimiento De Los Estudiantes De Educación Básica Superior De La Escuela De Educación Básica “Ciudad De Montalvo” Cantón Montalvo, Provincia De Los Ríos. - Silva Rivera Janet Del Rosario (2015)
One advantage of the tasks is to expand the level of knowledge acquired in school, hence the importance of the thesis topic "quality of homework and student achievement of higher primary school basic education "Ciudad de Montalvo", "sample was taken as reference to students of the 8th, 9th and 10th grade, where low quality tasks found, which is impacting the performance level of the students. In research methodology qualitative and quantitative applied, plus a descriptive and field study, a statistical process used to establish the results of the survey applied both teachers and students and parents, checking the following hypothesis: the quality of schoolwork if a significant impact on the performance of students in higher primary school "Montalvo City. With the results obtained through the research process developing a plan of action for teachers to improve the quality of student work by metering and integration of teaching arises.